2018
DOI: 10.5897/ijmms2017.1343
|View full text |Cite
|
Sign up to set email alerts
|

Determination, knowledge and prevalence of pregnancy-induced hypertension/eclampsia among women of childbearing age at Same District Hospital in Tanzania

Abstract: Several risk factors including hypertension are common complications of pregnancy with preeclampsia particularly associated with substantial risk to both the mother and fetus. This cross-sectional study involving quantitative approach was conducted in Same District Hospital in Tanzania. Data were collected from all pregnant women in the hospital using questionnaires. Respondents' knowledge on maternal mortality regarding preeclampsia included those who had no knowledge 60(60%), and those who had knowledge 40(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
5
17
3
Order By: Relevance
“…The ndings of the present study showed that those who had adequate knowledge about preeclampsia and eclampsia were 37.9%. The present ndings seem to be inconsistent with other research done in Same Moshi Tanzania [ 13 ]which found that 40% reported having adequate knowledge on preeclampsia and eclampsia [16].. The ndings might be due to the unplanned or absence of educational program regarding preeclampsia and eclampsia in the health facility as well as Community bases.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The ndings of the present study showed that those who had adequate knowledge about preeclampsia and eclampsia were 37.9%. The present ndings seem to be inconsistent with other research done in Same Moshi Tanzania [ 13 ]which found that 40% reported having adequate knowledge on preeclampsia and eclampsia [16].. The ndings might be due to the unplanned or absence of educational program regarding preeclampsia and eclampsia in the health facility as well as Community bases.…”
Section: Discussioncontrasting
confidence: 99%
“…This difference might be due to the geographical location where study was conducted as the current study conducted in Rural while the previous conducted in Urban, also it could be due to the differences in study population as the current study dealt with expecting couples both pregnant women and their male partners while the previous study focused mainly on pregnant women. This nding is in agreement with [ 13 ] ndings which showed 60.0%…”
Section: Discussionsupporting
confidence: 94%
“…These differences might be due to geographical location where the study conducted as the current study conducted in Rural while the previous conducted in Urban, also it could be due to differences in the study population as the current study dealt with both pregnant women and their male partners while the previous study focused mainly on pregnant women who are attending Antenatal clinic and get health education regarding their status. This finding also differ with [ 13 ] findings which showed 60.0% of the respondents reported to have no knowledge.…”
Section: Discussioncontrasting
confidence: 96%
“…In Malaysia, a study by Teng and Keng found only 18.4% of women to have adequate knowledge of PE [27]. Other studies by Savage and Hoho [25] and Eze et al [26] reported that 59% and 60% of Tanzanian women had inadequate knowledge of PE, respectively. Evidence indicates that adequate understanding of a disorder contributes to its prevention, control and management because patients’ knowledge regarding a disease positively influenced patient compliance to treatment and help abate complications associated with the disease [22, 23].…”
Section: Discussionmentioning
confidence: 99%